A Potential Biofertilizer—Siderophilic Bacteria Isolated From the Rhizosphere of Paris polyphylla var. yunnanensis - Wang, Yihan; Zhang, Gongyou; Huang, Ya; Guo, Min; Song, Juhui; Zhang, Tingting; Long, Yaohang; Wang, Bing; Liu, Hongmei (Frontiers in Microbiology, 2022)
Increasing demands for crop production have become a great challenge while also realizing significant reductions in synthetic chemical fertilizer use. Plant growth-promoting rhizobacteria (PGPR) are proven biofertilizers for increasing crop yields by promoting plant growth via various direct or indirect mechanisms. Siderophilic bacteria, as an important type of PGPR, can secrete siderophores to chelate unusable Fe3+ in soil for plant growth. Siderophilic bacteria have been shown to play vital roles in preventing diseases and enhancing the growth of plants. Paris polyphylla var. yunnanensis (PPVY) is an important traditional Chinese herb. However, reports about its siderophilic bacteria are still rare. This study firstly isolated siderophilic bacteria from the rhizosphere soil of PPVY, and identified by morphological and physio-biochemical characteristics and 16S rRNA sequence analysis. The dominant genus in the rhizobacteria of PPVY was Bacillus. Among 22 isolates, 21 isolates produced siderophores. The relative amount of siderophores ranged from 4% to 41%. Most of the isolates produced hydroxamate siderophores, and some produced catechol. Four isolates belonging to Enterobacter produced the catechol type, and none of them produced carboxylate siderophores. Intriguingly, 16 strains could produce substances that have inhibitory activity against Candida albicans only in iron-limited medium (SA medium). The effects of different concentrations of Fe3+ and three types of synthetic chemical fertilizers on AS19 growth, siderophore production and swimming motility were firstly evaluated from multiple aspects. The study also found that the cell-free supernatant with high siderophore units of AS19 strain could significantly promote the germination of pepper and maize seeds and the development of the shoots and leaves of Gynura divaricata (Linn.). The bacterial solution of AS19 strain could significantly promote the elongation of the roots of Gynura divaricata (Linn.). Due to its combined traits promoting plant growth and seed germination, AS19 has the potential to become a bioinoculant. This study will broaden the application prospects of siderophilic bacteria AS19 as biofertilizers for future sustainable agriculture.